Determinants of observing health protocols related to preventing COVID-19 in adult women: A qualitative study in Iran - Javad Yoosefi Lebni; Saeede Pavee; Mandana Saki; Arash Ziapour; Ahmad Ahmadi; Mehdi Khezeli (Frontiers Media S.A., 2022)
BackgroundThe best way to prevent COVID-19 is to observe health protocols. Therefore, identifying the reasons of following these protocols in order to plan and make intervention seems necessary. Therefore, the purpose of this study was to identify the determinants of observing health protocols related to prevention of COVID-19 among the Iranian adult women with a qualitative approach.MethodIn this qualitative study, the conventional content analysis approach was used. saturation was obtained after face-to-face semi-structured interviews with 38 women from Kermanshah who were selected through purposeful sampling and snowball sampling. Guba and Lincoln criteria were used for the strength of the research and Graneheim and Lundman method was used for its analysis.ResultsAfter analyzing the interviews, 5 categories, 12 subcategories and 110 initial codes were obtained. Categories and sub-categories were: 1- Individual factors (personality traits, health literacy about COVID-19); 2- Perceived risk having underlying disease in oneself and family, history of getting COVID-19 and death in close relatives; 3- Fear of the destructive consequences of the disease (concern about the economic consequences of getting the disease, concern about the treatment process); 4- Social and cultural factors (social monitoring, religious insight, ability to properly manage social interactions, impressionability from important others); 5- Environmental factors (supportive living environment, access to health and anti-infective materials).ConclusionIncreasing the adherence of adult women to health instructions related to COVID-19 requires interventions at different levels of individual, environmental and social, and without accurate knowledge of the customs and culture of a society effective interventions cannot be established.